Technology Savvy in ELT at one of the Private Junior High Schools in Cilacap: Is it important or not? - Erlin Satyarini (Proceedings Series on Social Sciences & Humanities, 2023)
The use of technology in daily life involves most people worldwide because technology can save time and effort. Technology in education is also critical to facilitating teaching and learning activities. Authentic material delivered with technology in learning can motivate students, one of which is language learning. The foreign language subject studied by junior high school students is English. This study aims to determine the use of information and communication technology (ICT) in teaching English (ELT), the media and applications used in teaching English, and the challenges of using information and communication technology. The research method used in this research is a qualitative approach. Data collection techniques in this study were interviews and questionnaires. The study results are based on consultations that most English teachers use ICT in ELT using a laptop, LCD, projectors, and internet media according to the required standards. Furthermore, the teacher also stated that all teachers had used media or applications to help them deliver learning materials to students so that students could more easily understand them. The teachers noted that these media and applications were instrumental in learning, where the press or applications immensely helped both teachers and students. The obstacle that causes not carrying out ICT-based education is that students cannot use cell phones for English learning media during offline learning at school because school regulations prohibit students from holding cell phones at school because, in reality, they open more to other things such as social media. Compared to the English material recommended by the teacher.